DESIGN OF NEAR FIELD COMMUNICATION PASSIVE ANTENNA FOR CIRCULAR SHAPED WEARABLE ITEMS (Pakistan Journal of Science, 2015)
The paper discusses proposed Near Field Communication (NFC) passive antenna design for circular and round shaped wearable items like rings, watches and wristbands. Several NFC passive tags were available in the market, which had different shaped antennas, incorporated into them. However, these tags were designed with specific shape and diameter and could not fit for most of the wearable items like rings, watches and wristbands etc. In order to overcome this problem, a customized NFC antenna for passive tags was designed, which could be suitable for circular shaped wearable items. Moreover, comparative analysis of proposed antenna with vendor made antenna had been performed to show how proposed customized antenna was much more efficient in performance.
Keywords: Near Field Communication; Mobile Communication; Antenna Design; Wearable Computing; Passive Tags; Radio Frequency Identification